2017
DOI: 10.1371/journal.pone.0173508
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of mycobacteria in sputum samples of pulmonary tuberculosis patients

Abstract: Pulmonary tuberculosis, the disease caused by Mycobacterium tuberculosis, still retains a top rank among the deadliest communicable diseases. Sputum expectorated during the disease continues to be a primary diagnostic specimen and also serves as a reservoir of bacteria. The expression pattern of mycobacteria in sputum will lead to an insight into bacterial adaptation at the most highly transmissible stage of infection and can also help in identifying newer diagnostic as well as drug targets. Thus, in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 55 publications
5
43
0
1
Order By: Relevance
“…Sputum becomes in turn the microenvironment where the transmissible stage of Mtb resides, whose microscopic phenotype and transcriptional profile suggested there is a shift in the lipid metabolism. Mtb recovered from sputum showed cytoplasmic lipid bodies revealed with auramine-nile red staining, significant overexpression of the large Kst-R regulon of cholesterol catabolism, overpression of tgs1 gene required for triacylglycerol synthesis and down-regulation of genes involved in phthiocerol dimycocerosate and phenol glycolipid synthesis indicating cell wall remodeling 23 , 24 . There is also evidence that hypercholesterolemia increases susceptibility to TB in mice 25 and a survey in Singapore found positive correlation between a cholesterol diet and an increased risk to active TB in Chinese population 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Sputum becomes in turn the microenvironment where the transmissible stage of Mtb resides, whose microscopic phenotype and transcriptional profile suggested there is a shift in the lipid metabolism. Mtb recovered from sputum showed cytoplasmic lipid bodies revealed with auramine-nile red staining, significant overexpression of the large Kst-R regulon of cholesterol catabolism, overpression of tgs1 gene required for triacylglycerol synthesis and down-regulation of genes involved in phthiocerol dimycocerosate and phenol glycolipid synthesis indicating cell wall remodeling 23 , 24 . There is also evidence that hypercholesterolemia increases susceptibility to TB in mice 25 and a survey in Singapore found positive correlation between a cholesterol diet and an increased risk to active TB in Chinese population 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Each functional group contained a different number of upregulated and downregulated transcripts (Figure 7D ). The hypergeometric test ( p < 0.05) was applied to determine the functional categories that were enriched in differentially expressed transcripts (Figure 7D ) (Leong and Kipling, 2009 ; Qureshi and Sacan, 2013 ; Sharma et al, 2017 ). The annotated list of identified M. tuberculosis transcripts with a potential role in invasion, transcriptional mechanism, environmental adaptation, and survival inside RPE cells at 3-dpi has been provided in Table 2 according to their functional categories as sorted by the TubercuList database ( http://tuberculist.epfl.ch ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, four genes ( Rv1971, Rv0169, Rv0592 , and Rv1967 ) belong to mammalian cell entry (mce) family protein that plays a crucial role in invasion and virulence of M. tuberculosis (Zhang and Xie, 2011 ). Recently, Rv1971 from this family was also reported to be upregulated in sputum samples of pulmonary TB patients (Sharma et al, 2017 ) and bioinformatically observed to be a highly antigenic protein involved in immune responses (Zhang et al, 2009 ). Interestingly, this gene was also detected in human IOTB samples (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acredita-se que essas famílias de parálogos sejam importantes fatores de virulência, atuando na evasão do sistema imune por meio da variabilidade genética (FISHBEIN et al, 2015;PHELAN et al, 2016). Em seguida destacamse os genes envolvidos em funções de housekeeping, como produção e conservação de energia (5,23%), citados como fundamentais para o momento da infecção no hospedeiro em análises de transcriptoma (SHARMA et al, 2017), transporte e metabolismo de lipídeos (4,62%), que contém genes essenciais para a sobrevivência nos macrófagos (FISHER;PLIKAYTIS;SHINNICK, 2002;RUSSELL et al, 2010), e transcrição (4,62%), que são primordiais para manutenção bacteriana no hospedeiro (RAMAN et al, 2004).…”
Section: Complexo Clonal Europeu 2 é Encontrado No Brasilunclassified